Student Perception of OBE-Based Learning Process: A Phenomenological Study on Master of Arabic Language Education Students - Amzaludin Amzaludin; Munirul Abidin (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2024)
This research aims to fill the gap with a focus on Perception, learning process, challenges faced by students and solutions in the OBE-based learning process. This study uses a phenomenological approach. Data collection through interviews and observations. The analysis of data obtained from interviews and observations will be analyzed using thematic analysis. This process includes transcribing interviews, encoding data, and identifying themes that emerge from the student experience. The results of the study on students' perception of the Outcome-Based Education (OBE)-based learning process in the Master of Arabic Language Education program, it can be concluded that:1. Positive Effects on OBE, 2. The Importance of Direct Practice,3. Interaction and Feedback. 4. The Need for a More Personal Approach,5. Availability of Learning Resources. Overall, OBE provides a positive learning experience for students, but it also needs to be balanced with adjustments in teaching methods and more personalized support to overcome existing challenges.